Pengaruh Pemberian Fraksi Daun Kemangi (Ocimum americanum L.) terhadap Berat, Diameter, Tebal Epitel Epididimis, Motilitas dan Viabilitas Spermatozoa Tikus Putih Jantan (Rattus norvegicus) - Louis, Stephanie Lexy; Salni, Salni; Nita, Sri (Politeknik Kesehatan Tanjungkarang, 2019)
Infertility is one of the reproductive problems that may affect both male and female. In a male, the occurrence of reproductive problems may be due to abnormal spermatogenesis processes and anatomic disorder. Kemangi leaves are an aphrodisiac it contains some secondary metabolites like flavonoid, steroid, tannin, and saponin. The objective of the present research was to determine the effect of feeding fractions of kemangi leaves (Ocimum americanum L.) on the epididymis weight, diameter, and epithelial thickness and the spermatozoa motility and viability of white male rat (Rattus norvegicus). The research was an experimental one, with posttest only group design. The research design used a Completely Random Design. The research sample consisted of 24 furrow white male mice Sprague Dawley, 60-74 days old, divided to control group, a fraction of n-hexane, a fraction of ethyl acetate, and a fraction of water-ethanol. The dosage used for the treatment group was 100 mg/kgBB/day, and the control group was given CMC 1%. The result of data analysis by using a One-Way Anova test showed that there were increases in the weight and diameter of the epididymis in the treatment group as compared to that of the control group (p=0,000). Likewise, both epididymis epithelium thickness and spermatozoa viability in the treatment group increased as compared to that of the control group (p=0.001), while spermatozoa motility was p=0,002. It could be concluded that the fractions of kemangi leaves increased the weight, diameter, and epithelium thickness of epididymis and spermatozoa motility and viability in-furrow white male rat Sprague Dawley.